Old Russian Cross-domed Churches with Corner Piers in the Late 14th — Early 15th Centuries. On the Origins of the Architectural Type in the Context of Byzantine and Balkan Architecture - Trushnikova, Alexandra V. (Actual Problems of Theory and History of Art, 2025)
The article invites the reader to look afresh at the origins of Old Russian cross-dome churches with corner piers. In the issue of the architectural form analysis we are to assume that numerous Byzantine and Balkan churches of the particular type should not be considered as the direct source of those in Moscow princedom. The latter can be rather interpreted in terms of the fraternity of the architecture development in these countries. The nature of Old Russian churches is defined as native Russian, conveying both the features of the Moscow architectural tradition in its making and the Hesychastic ideas behind visual forms. Presumed dating is late 14th — early 15th cc.